LYMPH NODES MORPHOLOGICAL CHANGES AND BREAST CANCER SUBTYPES IN PREDICTION OF METASTASES - Akhundova, J.N.; Amirova, M.F. (World of Medicine and Biology, 2024)
In this study, breast cancer patients aged 24–75 (53.9±0.8) were fully examined, and breast cancer receptor status immunohistochemical analysis was made by Allred scale. Lymph node’s size, shape, structure were recorded according to an ultrasound exam on “LOGIQ C5-Premium” (2012). The statistical analysis of obtained results was carried out using SPSS-26 software package. The sensitivity and specificity of indicators studied were shaped by ROC statistical analysis. The study results showed a significant association of subtypes as well as receptor expression with tumor metastasis to axillary lymph nodes. We found that HER2+ is the most aggressive breast cancer subtype in terms of tumor malignancy and morphological changes in axillary lymph nodes, leading to complete destruction of the node cortex structure, and therefore axillary lymph nodes in this subtype must be removed during surgical resection of primary cancer foci without fail.